How do pre-service teachers deliver their instruction during teaching practicum?: Voice from EFL classrooms - Dwiniasih Dwiniasih; Indri Deviriani Khumaeroh (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
For decades, questioning about effective method in a teaching learning process has been considered consistently in educational research. The existence of revised curricula forces teachers to renew or improve the teaching method used refers to the current edition. In fact, the teachers keep their teaching method caused of several concerns. Considering to the current issues, this study aims to investigate the teaching method applied by student teacher during teaching practicum, whether they tend to use modern or traditional teaching method. The participants of this study is ten learners of the eight grader at junior high school whose teacher is student teacher that conducting teaching practicum in their class. Since it is case study, student observation checklist and semi-structured interview were applied in gaining the data. The result revealed that the teaching method used by student teacher is modern method, even though; she combined it with conventional method incidentally